Quality Development of Policy Model for MTs Teachers - Putra Mahendra Gunawan Nasution; Wandana Simatupang; Syafaruddin Syafaruddin; Makmur Syukri (Universitas Pahlawan Tuanku Tambusai, 2022)
Quality is an absolute image that must be owned by every educational institution. In general, quality can be seen from the accreditation of educational institutions and academic services. Likewise, graduates are a reflection of the quality of educational institutions. One of the absolute factors to produce quality graduates is to support the development of teacher quality. This study aims to describe the policy model for developing the quality of MTs teachers in Central Tapanuli. The research approach is a qualitative type, with a descriptive study method. Data was collected using observation, interview, and document study techniques. Furthermore, data analysis uses data reduction techniques, data presentation, and data verification (to draw conclusions). Test the validity of research data using data triangulation techniques. The results of this study conclude that teachers have an important role in the progress of madrasas, the quality of teachers can be seen from the model of teacher quality development policies implemented in madrasas. The leadership of MTsN 1 and MTsN 2 in Central Tapanuli Regency implemented policies in the form of teacher quality improvement models according to needs, teacher quality development policies according to government policies, and instilling teacher discipline. Teachers are required to have high academic qualifications, and meet (four) competency standards, namely pedagogic, personality, social, and professional competencies. The teacher quality development policy at MTsN 1 and MTsN 2 Tapanuli Tengah has been implemented well, this can be seen from the ability of the madrasa principal to regulate all madrasa policies and programs so that the quality of education in Central Tapanuli can continue to improve.